Analisis Asuransi Pertanian di Indonesia : Konsep, Tantangan dan Prospek - Djunedi, Praptono (Pusjar SKPP Lembaga Administrasi Negara, 2016)
Agriculture is one of the important sectorfor Indonesia. However, the sector is vulnerable to various risks that may impact on the fluctuation of the income of farmers. Related to this, through Law No. 19 of 2013, the government seeks to protect farmers, one of which is through agricultural insurance. As a start-up country, the problem faced is how to develop agricultural insurance in Indonesia. Related to that, this study aims to (1) describe the concept of agricultural insurance, (2) describe the challenges faced to develop agricultural insurance, and (3) explain how the prospect. Some of the challenges can be grouped into four challenges, namely institutional, financial, technical and operationalchallenges. For the good prospect in the future, implementation of agricultural insurance is proposed to (1) gradually increase the allocation in state budget, (2) develop technical rules which include agricultural insurance scheme in compulsory basis, (3) encourage the relevant parties to commit in developing agricultural insurance (4) assign to the state-owned insurance as providers and distributors of agricultural insurance as well as a role as reinsurance agency, (5) assess the integration between the agricultural insurance scheme and agricultural services received by farmers (subsidized fertilizer, subsidized seed, and social assistance).Keywords: farmer, risk, agricultural insurance, premium subsidySektor pertanian merupakan salah satu sektor yang penting bagi Indonesia. Namun, sektor ini rentan terhadap berbagai risiko yang dapat berdampak pada berfluktuasinya pendapatan para petani. Terkait dengan hal ini, melalui Undang Undang Nomor 19 Tahun 2013, pemerintah berupaya melindungi petani, salah satunya adalah melalui asuransi pertanian. Sebagai negara start-up, permasalahan yang dihadapi adalah bagaimana cara mengembangkan asuransi pertanian di Indonesia. Terkait hal itu, tujuan kajian ini adalah (1) memaparkan konsep asuransi pertanian, (2) memaparkan berbagai tantangan yang dihadapi untuk mengembangkan asuransi pertanian, dan (3) menjelaskan bagaimana prospeknya. Beberapa tantangan yang dihadapi bisa dikelompokkan menjadi empat tantangan yakni tantangan institusional, finansial, teknis dan operasional. Agar implementasi asuransi pertanian memiliki prospek yang baik, diusulkan agar (1) meningkatkan alokasi dana implementasi asuransi pertanian dalam APBN secara bertahap, (2) menyusun aturan teknis yang diantaranya mengatur kepesertaan asuransi pertanian bersifat wajib, (3) mendorong pihak terkait sesuai dengan perannya berkomitmen mengembangkan asuransi pertanian, (4) memberi penugasan kepada BUMN asuransi sebagai penyedia dan penyalur asuransi pertanian serta berperan sebagai lembaga reasuransi, (5) mengkaji pengintegrasian antara program asuransi pertanian dengan layanan sektor pertanian yang diterima petani (pupuk bersubsidi, benih bersubsidi, dan bantuan sosial).Kata kunci: petani, risiko, asuransi pertanian, subsidi premi.